Criminalizing Civil Law Actions of Default into Criminal Acts of Fraud: A Human Rights Perspective - Yonatan; Wijayanta, Tata; Sugiri, Bambang; Sukarmi; Sulistio, Faizin (Universitas Airlangga, 2024)
The terms